Analyzing the literature on education governance over the last 71 years (REGE Revista de Gestão, 2023)
Purpose: this article results from a survey on national and international research articles published from 1947 to 2018, that aimed to produce a theoretical framework and description of education governance.Methods: the study was based on bibliographic research techniques. Its bibliometric analysis (Pritchett, 2001) focused on three structural indicators: 1) keywords, 2) most relevant journals, and 3) most productive researchers. A survey was made targeting national and international research articles on education governance published from 1947 to 2018 as available on Scopus.Results: the survey pointed out the fundamentals of the education governance dimensions as posited in Hufty’s (2011) Governance Analytical Framework, namely: problems, social norms, actors, nodal points, and processes.Originality: the study provides the theoretical framework for establishing operational definitions of aforementioned dimensions that can be used in an education governance assessment instrument.